Isolation of tobacco SSU genes: characterization of a transcriptionally active pseudogene. - O'Neal, J K (1987)
Genomic clones containing three genes for the small subunit (SSU) of ribulose bisphosphate carboxylase were isolated from tobacco. Detailed analysis was performed on two of these clones to give a clearer picture of this multigene family in tobacco. This analysis demonstrated that one of the clones contained a pseudogene that was unusual in that it was transcriptionally active. This is the first transcriptionally active pseudogene that has been reported in plants. In addition, another clone was found to contain coding sequences which are 100% homologous to a previously-cloned tobacco SSU gene (Mazur, B.J. and Chiu, C-F. [1985] Nuc. Acids Res. 13, 2372-2386), indicating that gene duplication and/or gene conversion may have played a role in the evolution of the tobacco SSU family.